Production of Black Garlic Assyifa made by the Utsman Bin Affan Islamic Boarding School, Pantai Labu District use Thermolysis Equipment - Sebayang, Nur Ulina Warnisyah; Hidayat, Benny; Raju; Kirana Aulia Rahma; Suranti Pratiwi; Corrady Noveindo Tanwie; Muhammad Syahid Zidan (Talenta Publisher, 2024)
Black Garlic is a product resulting from the thermolysis of garlic which is highly nutritious and has many benefits for the health of the human body. The problem that occurs is that black onion products are very rare and the price is very expensive. Limitations regarding equipment and from marketing and social aspects of the community include knowledge in producing black garlic, as well as marketing it to be able to increase partners' income sources. So far, partners have only used a simple method, namely an electronic rice cooker (Rice Cooker). The solution is to increase public understanding about the properties of black garlic and increase awareness of production so that it can get added value in the form of income if sold to the Utsman Bin Affan Islamic Boarding School. By using a thermolysis device with a capacity of 30 kg, it is possible to increase the quality and production of black garlic. The aim of the PkM implementation activities for the DRTPM Community Based Empowerment scheme in 2024 is to improve the quality of Black Garlic made by Pondok Tahfizh Utsman Bin Affan Pantai Labu by utilizing a thermolysis tool so that it can increase the level of income for partners. This service activity resulted in the production of 30 kg of black garlic on the 12th day of thermolysis with visualization results such as a slightly chewy texture, an even black color throughout, and a distinctive black garlic smell. The organoleptic results of black garlic have a taste that is dominated by sweetness and is slightly sour. The next plan in this service is to help partners in the packaging and marketing process using social media technology.